Pengaruh Retribusi Terhadap Pertumbuhan Ekonomi Simalungun - Pawer Panjaitan; Darwin Damanik; Ahmad Ashadi; Demak Angelita Purba; Putri Kharunissa; Widyia Mayasari Damanik (CV. Ulil Albab Corp, 2025)
This study aims to analyze the effect of levies on the economic growth of Simalungun Regency. Levy is one of the important sources of regional income for economic development, and its effective management can make a significant contribution to regional economic growth. This study uses secondary data obtained from the Central Statistics Agency (BPS) and the Simalungun Regency Government, and uses a simple linear regression analysis method to determine the relationship between levies and the Simalungun GRDP (Gross Regional Domestic Product). The results of the study indicate that levies have a positive effect on the economic growth of Simalungun Regency, although with a relatively small level of influence. This shows that good management of levies can support other economic sectors, but there needs to be an effort to increase efficiency and effectiveness in collecting levies so that they can be more optimal in supporting economic growth. In addition, other factors such as investment and productive sectors also play an important role in driving regional economic growth. This study provides recommendations to the Simalungun Regency Government to improve the management and utilization of levies as a more optimal source of regional income.